ANALISIS KOORDINASI PROTEKSI OVERCURRENT RELAY PADA TRAFO 5 GARDU INDUK CEMPAKA 150/20KV - Muhammad Afdal; Mahfudz Shidiq; Tri Nurwati (Jurnal Mahasiswa TEUB, 2022)
Relay is a tool that helps the protection system on the electric power network to check electrical equipment from disturbances that can damage the equipment, such as short circuit faults. Relays are divided into several types, one of which is the Over Current Relay (OCR). The OCR has the function of an electric power equipment function from short-circuit faults of phases. OCR has several different characteristics, such as the IEC inverse standard and the ANSI inverse standard. Each OCR characteristic has a difference in the basic formula and the resulting output curve. In IEC standard characteristics, the output of the relay is in the form of an L curve, that is, the greater the setting time, the greater the setting current in the relay. The substation has several transformers, each of which has two OCR relays, namely an OCR relay on the high voltage section (150kV) and an OCR relay on the middle low section (20kV). ETAP software is an application that can determine the coordination and output value of the work relay, making it easier to simulate relay work. However, if the relay simulation does not work according to the provisions, the settings on the relay can be changed to get the appropriate value. The Particle Swarm Optimization (PSO) method is one method that can improve the setting value on the relay so that it can work according to the provisions set by PT. PLN (Persero). In this study, the relay working simulation uses ETAP software and uses the PSO resetting relay method. The result of the travel time between the 150kV and 20kV sides of transformer 5 before using the PSO method is 3.05s on the 150kV side and 2.72s on the 20kV side, while before using the PSO method it is 3.4 on the 150kV side and 3.02s on the 20kV side. The time intervals before using and before using PSO were 0.33s and 0.38s. Based on the Manual of Conductor Protection and Control Maintenance, the delay between relays is 300-800 milliseconds. Therefore, the delay interval on the transformer relay 5 has worked well with using the PSO method or not according to the existing protection guidelines. Keywords — Relay, Over Current Relay, time setting, current setting, delay time, ETAP , particle swarm optimization.